Improving self-regulation and executive functioning skills in primary school children in a remote Australian Aboriginal community: A pilot study of the Alert Program®. Issue 1 (April 2019) - Wagner, Bree; Olson, Heather Carmichael; Symons, Martyn; Mazzucchelli, Trevor G; Jirikowic, Tracy; Latimer, Jane; Watkins, Rochelle; Cross, Donna; Boulton, John; Wright, Edie; Carter, Maureen; Bruce, Kaashifah; et al.
Self-regulation and executive functioning impairments are common in children with fetal alcohol spectrum disorder. Given the high rates of fetal alcohol spectrum disorder identified amongst children living in the remote Fitzroy Valley region of Western Australia, the Alert Program® was identified as a culturally safe intervention for use in local primary schools. Researchers collaborated with Aboriginal Elders, community members, and staff from a Fitzroy Valley primary school to trial the Alert Program®. Teachers were trained to deliver eight Alert Program® lessons to children in class. Self-regulation and executive functioning were measured using teacher and parent/caregiver questionnaires three times. Data were analyzed using repeated-measures ANOVA. Teacher-led delivery of the Alert Program® was feasible in a region with high fetal alcohol spectrum disorder rates. As measured by teacher and parent/caregiver ratings, this curriculum may improve the self-regulation and executive functioning of children for some outcomes and provide sustained effects for some children. This community partnered pilot research, evaluated a school-based program to reduce the behavioral impact of fetal alcohol spectrum disorder, and informed design of a larger trial across eight Aboriginal community schools.